2000
DOI: 10.1001/archinte.160.6.817
|View full text |Cite
|
Sign up to set email alerts
|

Payer Status and the Utilization of Hospital Resources in Acute Myocardial Infarction

Abstract: This report suggests significant variation by payer status in the management of AMI throughout the United States, but no important differences in mortality among the 3 largest payer groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
68
0
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 20 publications
8
68
0
4
Order By: Relevance
“…This reflects previous reports on this topic. [6][7][8][9] Also similar to prior studies, 35,36 payor status was associated with PLOS in our analysis. Because maintaining airway pressures of 10 cm H 2 O has been observed to significantly reduce atelectasis, pneumonia, and reintubation, 37,38 prophylactic continuous positive airway pressure may benefit COPD patients following CABG.…”
Section: Discussionsupporting
confidence: 86%
“…This reflects previous reports on this topic. [6][7][8][9] Also similar to prior studies, 35,36 payor status was associated with PLOS in our analysis. Because maintaining airway pressures of 10 cm H 2 O has been observed to significantly reduce atelectasis, pneumonia, and reintubation, 37,38 prophylactic continuous positive airway pressure may benefit COPD patients following CABG.…”
Section: Discussionsupporting
confidence: 86%
“…Further disparities in PCI utilization were revealed with private insurance holders were more likely to receive PCI as compared to government sponsored insurance holders (Medicare/Medicaid). Similar results have been demonstrated by Canto et al [34] in ACS patients. Our study also supported the "weekend effect" leading to less PCI on patients admitted during weekend as compared to weekdays and as predicted mortality is higher in these patients.…”
Section: Discussionsupporting
confidence: 91%
“…In a study of inpatient hospital resource use, Canto et al 33 observed that Medicaid-insured patients with acute myocardial infarction received fewer reperfusion therapies, underwent fewer invasive cardiac procedures, and had longer hospitalizations than Medicare-insured patients. Although these procedures have a discretionary component, they also may be less likely for patients who are in poor health.…”
Section: Discussionmentioning
confidence: 99%